Post-Ghazali Islamic Philosophy in the Sunni and Shi‘ite Traditions - A. Haris, Khalif Muammar; Febrian, Rizky (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
This study refutes the unfounded yet prevalent view among Western scholars and some contemporary Muslim scholars that Islamic philosophy has declined after al-Ghazālī due to his vehement critique of the philosophers. This study supports the previous studies by George Saliba and Frank Griffel who criticised the decline narrative and argued that Islamic philosophy and science continue to thrive after al-Ghazālī. Moreover, this study gives a general overview of the development of intellectual sciences which include works on metaphysics, epistemology, logic, ethics and politics both in the Sunni and Shiʻite traditions, and especially in the Malay world. Contrary to the decline narrative, the study shows that the Sunni epistemic framework which was crystalized in al-Ghazālī’s work contributed positively to the development of Islamic philosophy. His critique of Aristotelianism should be considered part of the Islamisation of Greek philosophy, and his works laid down a robust foundation for the development of intellectual sciences in the Islamic world.